Canine atopic dermatitis a look at current treatments (Research, Society and Development, 2022)
Canine Atopic Dermatitis is a chronic, inflammatory and pruritic skin condition, which is affected by several factors, which may be associated with genetic predisposition and changes in the epidermal barrier and which have a prevalence between 10% of the canine population, being the second most frequent allergic disease. The therapeutic approach takes into account several factors, such as seasonality, distribution and amount of affected skin, in addition to the severity of the lesion and stage of the disease, the patient's conditions, which can be topical or systemic, with a multimodal focus that includes the use of antipruritic drugs, allergen-specific immunotherapy and drugs that cause restructure the skin barrier and its microbiota. To highlight the current therapeutic alternatives for CAD. This is a literature review study, carried out in Pubmed, Scielo, Lilacs and Bireme databases with the keywords: Dermatology; Allergy; Canine Atopic Dermatitis. Therapeutic management of CAD is multifaceted and interventions should preferably be combined. The veterinarian must also remember that after evaluating, he must inform and discuss with the animal's owner about the possibilities and therapeutic choice so that he understands the benefit of each recommended intervention and whether the modality will be single or combined. Polytherapy and the use of drugs with fewer harmful side effects to the animal are recommended. Use protocols that help to restore the skin barrier and avoid allergens, as well as consider the cost of drugs and the financial conditions of the owner.